Carlos García Gual, “El Zorro y el Cuervo”. Estudios sobre las fábulas: Madrid, FCE, 2016, 164 p. ilus.; 21 x 14 cm - (Colección Antropología), ISBN 978-84-375-0751-4 (Argos, 2018)
Reseña
Keywords: Carlos García Gual